The Effect of Feeding Process Stimulation on Oral Preparedness Readiness in Premature Infants - Endah Dessirya; Herlina Herlina; Wahyuni Wahyuni; Iin Pusparini; Mustaqimah Mustaqimah; Dewi Hayati (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND: Most preterm infants do not have proper sucking, swallowing, and breathing coordination which caused  delay in oral feeding readiness. OBJECTIVE: The objective of this study was to analyze the influence of feeding stimulation on the readiness of premature infant’s oral feeding. METHOD: This study was a true experimental study that involved 44 preterm infants born between 32-34 weeks of gestational age, devided in two groups. Twenty two infants in the intervention group received positioning (mid-line control symmetric) and oral feeding stimulation, while the control group received only positioning intervention. Oral stimulation was given 8 times a day for 7 days, before starting the oral feeding program. Oral feeding readiness was measured by using a modified early feeding scale (EFS) instrument on the first and the seventh days. Data analysis using t-test dependent, independent t-test, and Mc Nemar test. RESULT: The results showed that there was a significant effect of the intervention on EFS score (p <0.001) and also on preterm infant’s oral feeding readiness (p = 0.002). The results also showed that there was an effect of intervention on the length of stay (p=0.001). CONCLUSION: Early oral feeding stimulation improves the infant’s oral feeding readiness and shortens the infant’s length of stay. Researchers recommend stimulation of the feeding process as an independent nursing intervention in caring for premature infants.